Analysis of Knowledge and Perception of Implementation of Informed Consent in Patient Pre Operations in HVA Toeloengredjo Pare Hospital - Rudy Surya K. Hedo (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
Incompleteness and inaccuracy of charging informed consent in patient’s pre-operation is a problem related to patient safety, professionalism, behavior, and quality culture. The research objective is to analyze the knowledge and perception of the Implementation of Informed Consent in Patients with Pre-Operations at RS HVA Toeloengredjo Pare. Design Cross-sectional study using. The population is the preoperative patient at RS HVA Toeloengredjo Pare.exclusion criteria using simple random sampling technique. The independent variable of research is the knowledge and perception of the patient, and the dependent variable of the study is the completeness and accuracy of implementation preoperative patient's informed consent. Data were collected by questionnaire and a check list, then the data were analyzed using linear regression with a <0.05 and cross tabulation analysis. The results showed most respondents have sufficient knowledge of as many as 69 respondents (44,8%), most respondents have the perception that quite as much as 82 respondents (53.2%), linear regression showed that the variables significantly affect the perception of completeness informed consent (p = 0.000) and in the knowledge variables significantly affect the accuracy of informed consent (p = 0.006). The conclusion of this study is to increase knowledge and perception, will support the implementation of the informed consent form completeness and accuracy of informed consent.